Pengaruh Kompetensi Dan Komitmen Pada Tugas Terhadap Kinerja Karyawan Pada Hotel Dharma Deli Medan - Faustyna Faustyna (JURNAL ILMIAH MANAJEMEN & BISNIS, 2014)
This research aimed to find out the correlation between competence and commitment  to employee performance. Variable competence and commitment simultaneously and partially had positive influence on employee performance.  That means that company have to increase employee performance by increasing the competences and commitment, through any program that should be developed.